2004
DOI: 10.1007/s10803-004-5283-1
|View full text |Cite
|
Sign up to set email alerts
|

Relative Carnitine Deficiency in Autism

Abstract: A random retrospective chart review was conducted to document serum carnitine levels on 100 children with autism. Concurrently drawn serum pyruvate, lactate, ammonia, and alanine levels were also available in many of these children. Values of free and total carnitine (p < 0.001), and pyruvate (p = 0.006) were significantly reduced while ammonia and alanine levels were considerably elevated (p < 0.001) in our autistic subjects. The relative carnitine deficiency in these patients, accompanied by slight elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(127 citation statements)
references
References 40 publications
9
115
2
1
Order By: Relevance
“…60 There have also been a few isolated reports of a mitochondrial and/or metabolic abnormality (eg, carnitine deficiency) being associated with an ASD, but the significance of these reports is not clear. 133 Increased and decreased levels of T lymphocytes, immunoglobulins, and antibrain autoantibodies in the systemic circulation have been reported. 134 These have been observed chiefly in retrospective case studies of patients with idiopathic ASDs, but systematic prospective studies have confirmed neither their existence nor their relevance.…”
Section: Table 2 Diagnostic Criteria For 29980: Asperger's Disorder mentioning
confidence: 99%
“…60 There have also been a few isolated reports of a mitochondrial and/or metabolic abnormality (eg, carnitine deficiency) being associated with an ASD, but the significance of these reports is not clear. 133 Increased and decreased levels of T lymphocytes, immunoglobulins, and antibrain autoantibodies in the systemic circulation have been reported. 134 These have been observed chiefly in retrospective case studies of patients with idiopathic ASDs, but systematic prospective studies have confirmed neither their existence nor their relevance.…”
Section: Table 2 Diagnostic Criteria For 29980: Asperger's Disorder mentioning
confidence: 99%
“…Carnitine deficiency has been noted in mitochondrial disease, fatty acid oxidation defects, and valproic acid treatment. 117 A retrospective chart review of carnitine levels in children with ASD identified lower carnitine levels and higher alanine and ammonia levels, compared with the laboratory reference range mean, 117 although these children did not have clinical signs of mitochondrial disease. No studies have evaluated treatment effects of carnitine.…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…In several studies of individuals presenting with autism, but without classical mitochondrial disease, increased ammonia has also been described; this led some authors to conclude that MtD was present [40,63,64] . Typically, these ammonia levels are not nearly as elevated as those that have been observed in some conditions that can cause autism, such as urea cycle disorders [66] .…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%
“…However, many of these laboratory abnormalities have also been described in autistic individuals with MtD and without any other evidence of classical mitochondrial disease. For example, elevated blood lactate levels consistent with MtD have been described in numerous autistic individuals [29,40,[61][62][63][64][65] , sometimes affecting as many as 43% of children with autism studied when compared to neurotypical children [17] . In one study, ASD children with an elevated blood lactate level underwent deltoid muscle biopsy and approximately 35% (5 out of 14) were found to have classical mitochondrial disease [22] .…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%